New in town - Brooks, Paul.; Rance, Kenneth 1970-.; Cox, C Jay 1962-.; Elmer, Jonas 1966-.; Zellweger, Renee 1969-.; Connick, Harry 1967-.; Simmons, J K 1955-.; Conroy, Frances 1953-.; Hogan, Siobhan Fallon 1961-.; Lions Gate Films; Gold Circle Films; Epidemic Pictures; et al. (Pasig City Viva Video, Inc., 2009)
A high-powered consultant in love with her upscale Miami lifestyle is sent to a small Minnesota town, in the middle of nowhere, to oversee the restructuring of a blue collar manufacturing plant. She endures a frosty reception from the locals, along with the icy roads and freezing weather. She warms up to the small town's charm, and eventually finds herself being accepted by the community. When she's ordered to close down the plant and put the entire community out of work, she's forced to reconsider her goals and priorities. Now she needs to find a way to save the town.
Title from container.
Director of photography, Chris Seager ; editor, Troy Takai ; music, John Swihart ; costumes designed by Darena Snowe, Lee Harper ; production designer, Dan Davis.
Renée Zellweger, Harry Connick, Jr., J.K. Simmons, Frances Conroy, Siobhan Fallon Hogan.
VCD.
Keywords: Industrial relations consultants -- Florida -- Miami -- Drama; Factories -- Minnesota -- Drama; Blue collar workers -- Minnesota -- Drama; Man-woman relationships -- Minnesota -- Drama; Feature films; Romantic comedy films; Films for the hearing impaired; Drama